Teaching literature with Moodle in the Bachelor of Education - María Guadalupe Veytia Bucheli; Jesús Alberto Leyva Ortiz (Universidad de Guadalajara, 2017)
This paper relates the experience acquired with the usage of Moodle assisting the teaching -learning process in the Literature Appreciation Seminar 1 given to fifth semester students in the Spanish Major from the Benemérita y Centenaria Escuela Normal del Estado de San Luis Potosí. The purpose if this work is to reflect about the findings obtained based on a qualitative and quantitative analysis from the information gathered with the application of a semistructured questionnaire. The results obtained reflect student's weekly work, mostly to comply with assignment submissions. In a general view, it is noticed that pupils find themselves motivated working with this learning tool. It is also seen as an opportunity area, the reinforcement of this kind of learning focusing more on collaborative work and managing more options from the Moodle platform. Some of the conclusions from this paper are the importance of incorporating Learning Management Systems in pre-service training teaching from a didactic, constructive and ecological perspective, as well as, allowing students to work with ICT by creating significant learnings using virtual environments in order to be able to transfer them to other contexts.